Comparing trends in BMI and waist circumference - Walls, H.; Stevenson, C.; Mannan, H.; Abdullah, A.; Reid, Christopher; McNeil, J.; Peeters, A. (2011)
The nature of excess body weight may be changing over time to one of greater central adiposity. The aim of this study is to determine whether BMI and waist circumference (WC) are increasing proportionately among population subgroups and the range of bodyweight, and to examine the public health implications of the findings. Our data are from two cross-sectional surveys (the US National Health and Nutrition Examination Studies (NHANES) in 1988-1994 (NHANES III) and 2005-2006), from which we have used samples of 15,349 and 4,176 participants aged =20 years. Between 1988-1994 and 2005-2006 BMI increased by an average of 1.8kg/m2 and WC by 4.7cm (adjusted for sex, age, race-ethnicity, and education). The increase in WC was more than could be attributed simply to increases in BMI. This independent increase in WC (of on average, 0.9cm) was consistent across the different BMI categories, sexes, education levels, and race-ethnicity groups. It occurred in younger but not older age groups. Overall in each BMI category, the prevalence of low-risk WC decreased and the prevalence of increased-risk or substantially increased-risk WC increased. These results suggest that the adverse health consequences associated with obesity may be increasingly underestimated by trends in BMI alone. Since WC is closely linked to adverse cardiovascular outcomes, it is important to know the prevailing trends in both of these parameters.